Gerakan Islam Radikal di Sulawesi Selatan: Pola Rekrutmen dan Pola Gerakan Komite Persiapan Penegakan Syariat Islam (KPPSI) dan Laskar Jundullah - Karsono, Karsono (Pusat Kajian Keamanan Nasional (Puskamnas) Universitas Bhayangkara Jakarta Raya, 2018)
The Preparatory Committee for the Upholding of Islamic Law (KPPSI) was established on 28 May 2000. Laskar Jundullah is an autonomous body under the KPPSI, but there is no effective coordination between Laskar Jundullah and KPPSI. In recruitment, membership of the KPPSI takes place openly, whereas Laskar Jundullah is more closed. This research explains the relationship between the two organizations, intended as a reference model to understand radical religious movements in the region. The data was collected through interviews, literature reviews, papers, and related news. This study shows that an Islamic organization is not free from intact radical Muslim groups. Loose structure its even makes the organization more vulnerable to being used by radical groups.